Prevalência de atitudes e atividades de autocuidado em idosos diabéticos - Lucena, Adriana Lira Rufino de (2017)
Introduction: Diabetes mellitus is a metabolic disorder that needs self-care activities, in order to maintain its control. Objective: to analyze the relation of attitudes and activities for self-care in elderly people with diabetes mellitus in João Pessoa-PB. Methodology: it is a transversal study, quantitative, which was developed in a Basic Health Unit with 153 diabetic elderly people. The data collection was done between June and July, 2016. They were done descriptive statistical analysis, calculations of absolute and percentage frequencies, as well as measures of central and of dispersion tendency. In addition, comparison tests of averages were developed, considering a confidence interval of 95%, with a significance level fixed in p<0.05. The project was approved by the Research Ethics Committee of the Federal University of Paraíba, according to CAAE 54402216.4.0000.5188. Results: the socio-demographic data revealed that 89 (58.2%) elderly people were between 60 and 69 years, 116 (75.8%) were female members, 85 (55.6%) were married, 96 (62.7%) were without schooling, 147 (96.1%) were retired, 81 (52.9%) had 8-years diagnostic time, 93 (60.8%) had associated pathologies, and 121 (79.1%) had no complications. In the ATT-19 scores there was a variation from 43 to 76 points and average total score of 57.87. The clinical characteristics evidenced a statistically significant difference in relation to the average score of the ATT-19 and associated pathologies (p<0.002). As for the total score obtained in the ATT-19 and the average score of each question of the QAD questionnaire, it was evidenced the association between food orientation (p=0.097) and to take the medicines as recommended (p=0.063), the indicated number of tablets for diabetes (p=0.105) and the ingestion of sweets (p<0.003). Conclusion: the study permitted to reflect about the importance of investigating in the diabetic elderly people the self-care practices that are developed to cope with the disease and, thenceforth, to search for strategies in order to attend the emotional and clinical needs.